Evaluation of the Total Content of Phenols and Flavonoids in Two Different Extracts of Orbea wissmannii O. Schwart and their Toxic Effect on WI38 and HepG2 Cell Lines. - Mubarak, Ahmed Y.; al-attab, Bushra M.; Almaqtar, Maher A. (Journal of Amran University, 2023)
This study aimed at estimating the total phenolic content, total flavonoid content and evaluation of toxic effect of chloroform and aqueous methanol extracts of Orbea wissmannii against WI38 and HepG2 cell lines. Orbea wissmannii was collected from Qaren region near Amran governorate, Yemen. Chloroform and methanol extracts of whole parts of Orbea wissmannii were prepared by maceration and decantation. The total polyphenol content was estimated using Folin–Ciocalteau method. Aluminum chloride colorimetric method was applied for the determination of total flavonoid content. The cytotoxic activity was measured using the MTT assay. The total phenolic content of chloroform and methanol extracts was 70.21 mg GAE/g, 122 mg GAE/g respectively (milligrams of gallic acid equivalents per gram), while the flavonoid content was 21.80 mg QE/g and 54.24 mg QE/g respectively (milligrams of quercetin dihydrate equivalents per gram). Dependently, the two extracts significantly and concentratedly reduced the viability of lung tissue-derived fibroblasts (wi38) and human hepatoma cells (HepG2). The two extracts showed effective effect on HepG2 at 250, 500 and 1000 μg/ml, while the same extracts showed their effect on the WI38 at 500 and 1000 μg/ml. The toxicological properties shown by the extracts of this plant require further study to isolate and purify the active substances responsible for this high anti-cancer efficacy. Phytochemical investigation on chloroform/methanol extracts and their structures is recommended.